2015
DOI: 10.1007/s11270-015-2462-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Difenoconazole and Tebuconazole in Allium cepa

Abstract: Macroscopic (germination and root growth) and microscopic (mitotic index, chromosome, and nuclear aberrations) analyses have been used to determine the toxicity of environmental pollutants. To better understand the molecular mechanisms of mutation and their effects, molecular markers offer a key perspective, as they measure the direct effects of DNA mutagenic agents. The aim of this study was to evaluate the toxic potential of the fungicides difenoconazole (DZ) and tebuconazole (TZ) on Allium cepa. A reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 38 publications
6
21
1
8
Order By: Relevance
“…Hence, significant decreases in RG reflect the toxicity of the substance [32]. Evaluating the phytotoxicity of the triazolic active principles difenoconazole and tebuconazole, found in commercial fungicides, Bernardes and co-workers [33] found that the first did not affect the percentage of germinated seeds, similarly to what was observed in the present work.…”
Section: Cytotoxic and Phytotoxic Effectsupporting
confidence: 87%
See 1 more Smart Citation
“…Hence, significant decreases in RG reflect the toxicity of the substance [32]. Evaluating the phytotoxicity of the triazolic active principles difenoconazole and tebuconazole, found in commercial fungicides, Bernardes and co-workers [33] found that the first did not affect the percentage of germinated seeds, similarly to what was observed in the present work.…”
Section: Cytotoxic and Phytotoxic Effectsupporting
confidence: 87%
“…Root growth and initial development of the lettuce plantlet were significantly reduced only in three treatments (4a, 250 µg mL -1 ; 4b, 100 µg mL -1 ; 4e, 250 µg mL -1 ) with the triazoles evaluated here (Table 4), whereas tebuconazole and difenoconazole, in the work of Bernardes and co-workers 44 , had significant effects on the reduction of GSI and RG at all evaluated concentrations. It is worth noting, however, that the concentrations tested in the present work are one thousand times more diluted than those utilized by Bernardes and co-workers [33], which varied from 7 to 200 g L -1 .…”
Section: Cytotoxic and Phytotoxic Effectmentioning
confidence: 60%
“…As a triazole fungicide, TEB has been widely used in agriculture, leading to adverse effects on humans and wildlife (Sivikova, Dianovsky, Holeckova, Galdikova, & Kolesarova, ; Renzo et al, 2011; Castro et al, ; Bernardes, Andrade‐Vieira, Aragao, Ferreira, & Ferreira, ; Mercadante et al, ). The persistence in the environment and long half‐life mean that transgenerational investigation by parental exposure becomes very significant.…”
Section: Discussionmentioning
confidence: 99%
“…A hipótese de influência dos microrganismos no crescimento das plantas é corroborada pelo fato de que a emergência das plântulas, única variável que não representou um indicador de crescimento propriamente dito, não apresentou variações significativas nos diferentes períodos de exposição, tanto para o grupo controle, quanto para os demais tratamentos testados. De fato, a germinação de sementes tem se mostrado como o parâmetro menos sensível dentre os usualmente avaliados em testes de fitotoxicidade de agrotóxicos (SHAKIR et al, 2016), muito embora já tenham sido relatados efeitos negativos sobre tal variável diante de doses altas de abamectina e difenoconazol (BERNARDES et al, 2015;SHAKIR et al, 2016). BROWN, 2007;CHAPIN III et al, 2000;DE BELLO et al, 2010).…”
Section: Resultsunclassified
“…Embora tais produtos possam apresentar eficácia satisfatória em prevenir e combater pragas agrícolas, eles têm sido motivo de preocupação devido à sua baixa especificidade, ou seja, eles podem afetar tanto as pragas (organismos alvo), quanto outros organismos não alvo (BHAT, 2012;PIMENTEL, 1995;PIMENTEL;, tais como as próprias plantas em que são aplicados, ou outras plantas que não são o objetivo primário da pulverização (BERNARDES et al, 2015;DIAS, 2012;SHAKIR et al, 2016). Consequentemente, os agrotóxicos podem interferir nos processos de germinação e crescimento das plantas em virtude de diversos fatores, tais como a ação sobre fatores fisiológicos das mesmas, a toxicidade a organismos que são benéficos a elas e a interferência nos processos de absorção de nutrientes (FLETCHER, 1987;PETIT et al, 2012;SHAKIR et al, 2016).…”
Section: Conclusões E Consideraçõesunclassified